Pharyngeal airway changes after mono-maxillary advancement surgery - Stefanović Neda Lj.; Živković Sandić Marija; Martin Juan Palomo (Srpski Arhiv za Celokupno Lekarstvo, 2018)
Introduction/Objective. Maxillary or mandibular retrognathism are common dentofacial deformities treated by combined orthodontic-surgical treatment. Surgical maxillary or mandibular advancement changes the position and strain of surrounding structures, which may also affect pharyngeal airway dimensions. The aim of this study was to evaluate and compare three-dimensional pharyngeal airway space changes in patients treated with maxillary advancement and those treated with mandibular advancement. Methods. The sample consisted of 25 patients – 12 treated with maxillary advancement and 13 with mandibular advancement surgery. Nasopharyngeal (NP) volume, oropharyngeal (OP) volume, and the area of maximum constriction (AMC) in the OP were measured on cone beam computed tomography scans (2 mA / 120 kV / 12’’ FOV) taken before and at least three months after surgery. Paired samples t-test was used for analyzing statistical significance of changes (p ≤ 0.05). Results. Postoperative OP and NP volumes, as well as the AMC, increased insignificantly in both groups. Conclusion. Results suggest that mono-maxillary surgical advancement of the maxilla or the mandible increases pharyngeal airway dimensions.